REDEFINISI MADRASAH: MENGEMBALIKAN PRODUK HIBRIDA YANG USANG DENGAN MENAMBAHKAN UNSUR ISLAMI UNTUK MENINGKATKAN KEDALAMAN PENGETAHUAN AGAMA DAN MENINGKATKAN HASIL AKADEMIK - Ashar, Salim (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Religious education provided in madrasas, such as the schools themselves, is a hybrid product that combines subjects taught in traditional quran schools with modern pedagogies. Character, moral, and good behavior are the heart of Islam. All Islamic knowledge is directed at improving the behavior of insiders and outsiders and their relationship with God and humanity in general. Ethics is its own science in Islam and, in fact, the most important science for all advanced fields of knowledge is morals (straight characters). The general typology used to explain the authority of Islam more generally includes the division of authority based on knowledge (exoteric); access to the spiritual (esoteric) realm. It has been established from the Prophet and his colleagues that the transmission of ethical knowledge is the aim of Islam. the results of the analysis provide an overview in the class I elementary thematic book p. 10 "Try reclaiming the 4th principle of Pancasila in front of your friends alternately" added "the arguments in the al quran" and stated that Pancasila does not conflict with Islam; the second example "Parents help students show a variety of healthy foods at home" in elementary class I thematic book p. 25 improved "Parents help students show a variety of healthy foods" halal and good "that are at home and provide information on how to eat according to Islam", and so on, the point is when teacher presentations are replaced by interactions with students. At the same time, a student comes to be placed in the content: although in a form that is slightly but significantly altered, by connecting students to vague texts outside the class, different spaces to become subjects of a Muslim are produced. More specifically, analysis will show how comparisons, when used as a strategy for dealing with religion, achieve special meaning when combined with the incorporation of student experience.